Generalized Maximum Entropy Estimation of Linear Models. (March 2017) - Corral, Paul; Kuehn, Daniel; Jabir, Ermengarde
In this article, we describe the user-writtengmentropylinear command, which implements the generalized maximum entropy estimation method for linear models. This is an information-theoretic procedure preferable to its maximum likelihood counterparts in many applications; it avoids making distributional assumptions, works well when the sample is small or covariates are highly correlated, and is more efficient than its maximum likelihood equivalent. We give a brief introduction to the generalized maximum entropy procedure, present thegmentropylinear command, and give an example using the command.